Optic Nerve Diseases and its Systemic Associations - Rehman, Mubashir; Aftab, Akhundzada Muhammad; Khan, Sher Akbar; Shah, Asim Ali; Ahmad, Imran; Alam, Adnan (Pakistan Journal of Ophthalmology, 2017)
Purpose: To determine optic nerve diseases and its systemic associations. Study Design: Descriptive cross sectional study. Place and Duration of Study: Eye departments of Lady Reading Hospital Peshawar and Khyber Teaching Hospital Peshawar from Jan 2015 to Oct 2015. Material and Methods: A total of 44 patients were examined. Detailed history was taken from every patient after which complete ocular examination including recording of visual acuity, checking pupillary reactions and fundoscopy with special attention to optic nerve head appearance and recording of color vision and light brightness sensitivity was carried out. Specific ophthalmic and systemic investigations were performed. Results: Seven (15.91%) patients had NAION, 6 (13.64%) had demyelinating optic neuritis, 2 (4.54%) had toxic optic neuropathies, 2(4.54%) had nutritional optic neuropathy, 3 (6.82%) had pituitary macroadenoma and 3 (6.82%) had benign intracranial hypertension, 2 (4.54%) had arteritic anterior ischemic optic neuropathy, 2 (4.54%) Pseudo-Foster Kennedy syndrome, 1 (2.27%) had paraneoplastic syndrome, 1 (2.27%) had superior saggital sinus thrombosis, 1 (2.27%) had occipital lobe infarct, 1 (2.27%) had brain metastasis, 1 (2.27%) had craniopharyngioma, 1 (2.27%) had bilateral thalamic ischemia and1 (2.27%) had hydrocephalus. Conclusion: Patients presenting with optic nerve diseases may have serious systemic associations so for accurate diagnosis and management every patient presenting with optic nerve disease must be properly evaluated. Key words: Optic nerve, optic neuritris, optic neuropathy.